Pengaruh Kompensasi Islami, Kompetensi Syariah, dan Kecerdsan Spiritual Terhadap Kinerja Pegawai Badan Pusat Statistik Kabupaten Merangin - Yonie Septiya Ningsih, Rika; -, Habriyanto; Rahma, Sri (Islamic Economics Department, Faculty of Islamic Economics and Business, UIN SULTHAN THAHA SAIFUDDIN JAMBI, 2024)
This research aims to analyze the effect of Islamic compensation, sharia competence and spiritual intelligence on employee performance at the Merangin Regency Central Statistics Agency. This research was conducted at the Central Bureau of Statistics Merangin Regency. The sample is used in this research are all employees at the Merangin Regency Central Statistics Agency totaling 31 employees. The collection technique was carried out by distributing questionnaires to employees, using non-probabilty sampling, namely total sampling technique or saturated samples. This research uses quantitative research methods. The analysis technique uses instrument test, classical assumption test, and hypothesis testing hypothesis test with results showed that the independent variables (Islamic compensation, sharia competence, and spiritual intelligence) has a positive and significant influence on the dependent variable (employee performance). This is evidenced by partial t test with the value Islamic compensation (X1) 2,786 > 2, 052 significance level 0,052 < 0,05, sharia competence (X2) significance level 0,008 < 0,05, and spiritual intelligence (X3) 3,692 > 2, 052 significance level 0,001< 0,05. The results of the f test for Islamic compensation, sharia competence, and spiritual intelligence have a positive and significant effect on employee performance Merangin Regency Statistics Agency.